Real-Time Deployment of Pruned Volterra Algorithm for PAM4 Signals in a W-Band Wireless System - Zhu, Zonghui; Wang, Kaihui; Sun, Xinda; Zhang, Long; Gou, Yumeng; Meng, Yuanxiao; Chen, Yun; Yu, Jianjun (Journal of lightwave technology, 2024)
Nonlinear equalization technology is widely used in signal impairment compensation, among which Volterra equalizer is a commonly used method that can model and compensate for the linear and nonlinear parts of the system. However, the Volterra equalizer has high complexity and is difficult to implement in a field programmable gate array (FPGA). This paper proposes a decision-oriented least mean square (DD-LMS) Volterra algorithm and performs pruning operations on it. Compared with the traditional Volterra algorithm, this algorithm has faster convergence speed and does not require training sequences. Through pruning operations, the complexity and resource overhead of the Volterra-DDLMS algorithm are greatly reduced. This paper demonstrates an FPGA-based W-band wireless millimeter wave system with DD-LMS Volterra algorithm to improve performance. The receiving end uses 32-channel parallel Resample, Constant Module Algorithm (CMA) and pruned Volterra-DDLMS equalizer to process high-speed parallel PAM4 signals. The 14.7456 Gbit/s PAM4 signal was successfully transmitted within 40 meters of free space and met the 2.4 × 10 −2 soft decision forward error correction (SD-FEC) standard. Finally, PAM4 signal transmission system based on pruned Volterra showed good stability within a 1-hour measurement period, and its real-time measurement bit error rate (BER) performance was verified.